Trends of tactical performance analysis in team sports: bridging the gap between research, training and competition - Garganta, J. (Revista Portuguesa de Ciências do Desporto, 2009)
Performance in Team Sports is carried out through a long term and methodical training process planned to improve skills and competence required to deal with competitive demands. Despite that tactical constraint play a major role in Team Sports performance the history of its scientific analysis has been driven by physiological and biomechanical approach, paying little attention to the tactical behaviour of the players and team organisation. For coaches and researchers, tactical analyses can be helpful, since they offer the opportunity to identify match regularities and random features of game events. The information about performance is crucial to achieve individual and team efficacy, also because it constitutes a basic criterion for training process. Once tactical major features are identified, they can inform training and performance enhancement programs. Regardless the technological progress, the analysis of tactical performance in Team Sports remains an under-theorised field, since there was no significant amount of research undertaken to identify the most important factors underpinning performance. Thus, it seems relevant to find out concepts and methods allowing to assemble and to organise knowledge about game complexity and dynamic interaction properties of the teams. The main purpose of this paper is to point out that conceptual frame about tactical indicators in Team Sports should be a major orientation to bridge the gap between research, training and competition.